Novel ceramic paper structures for diesel exhaust purification - Leonardi, Sabrina Antonela (2018)
The catalytic combustion of diesel soot is addressed with flexible and structured “paper catalysts”. Two different series of catalysts were prepared either by drip impregnation or by a spray method to deposit a mixture of Co, Ba, and K or a mixture of Co and Ce onto SiO2-Al2O3 ceramic paper matrixes. In every case, CeO2 nanoparticles were added to bind the ceramic fibers. SEM images showed that the impregnation method generated catalytic particles concentrated as large chunks (> 10 μm), mainly at ceramic fiber crossings, whereas the spray method produced smaller catalytic particles (< 1 μm) well distributed throughout the ceramic paper. Besides, Co-Ba-K particles appeared better dispersed on the surface of ceramic fibers than Co-Ce due to the presence of K. Additionally, FTIR spectra showed the formation of O2 2− and O2 − species associated with CeO2 (binder) on the samples containing potassium which gave the Co-Ba-K-ceramic paper good catalytic properties, thus making the Co-Ba-K drop impregnated the best catalyst both considering activity and stability. Successive temperature programmed oxidation (TPO) runs up to 700 °C caused the formation of cobalt silicates in the catalytic ceramic paper prepared by the spray method, as indicated by TPR. The formation of these species was probably favored by the smaller size of cobalt particulates and their higher dispersion in the catalysts prepared by the spray method. This provoked the partial loss of the redox properties of Co3O4. TPR experiments also indicated the formation of BaCoO3 in Ba-containing ceramic paper, which could help in maintaining the catalyst activity after several TPO runs through the capacity of this mixed perovskite-type oxide to trap and release NOx.